The domains and demands of school social work practice a guide to working effectively with students, families, and schools - Kelly, Michael S. (Michael Stokely), 1968-; School Social Work Association of America (Oxford : Oxford University Press, 2008)
The demands of federal legislation like No Child Left Behind and state requirements for certification are making it increasingly necessary that school social workers demonstrate that they are highly qualified school-based mental health and social service professionals who can demonstrate outcomes that impact school bottom line issues.
Description based on print version record.
Includes bibliographical references and index.
Keywords: School social work -- United States; Evidence-based social work -- United States